ANALYZING HEGEMONY: FACTION SYSTEM IN VERONICA ROTH’S DIVERGENT - PRIMANANDA, ELMIRA (LANTERN (Journal on English Language, Culture and Literature), 2016)
This thesis entitled Analyzing Hegemony: Factions System in Veronica Roth’s Divergent has purpose to analyze the concept of hegemony by Antonio Gramsci and the formula of science fiction in Faction System that happens in a novel entitled Divergent by Veronica Roth. The method that is used in this research is contextual method by analyzing the intrinsic and extrinsic elements of the story through the library research. The analysis of intrinsic elements is used to analyze the formula of science fiction, while the analysis of extrinsic elements is used to apply the concept of hegemony by Antonio Gramsci. The Faction System is a kind of system that controls the life of people in the story. The people are divided into five categories that include five kinds of virtues; there is selflessness, honest, peaceful, intelligent, and fearless. The result of this thesis shows that the author of the novel reveals the two anomalies or the mysteries of the story into linear order. This thesis also concludes that the effect of hegemony that is done by the dominant group in the story causes people to live with the stereotype. The stereotype that is found in each category of people in the Faction System will cause the people to war.The conclusion shows that the Faction System cannot bring peace to society, because there is still discrepancy that creates opposition between people in the story.